Bruxism throughout the lifespan and variants in MMP2, MMP9 and COMT - Vieira, Alexandre R.; Scariot, Rafaela; Gerber, Jennifer T.; Arid, Juliana; Küchler, Erika C.; Sebastiani, Aline M.; Palinkas, Marcelo; Díaz-Serrano, Kranya V.; Torres, Carolina P.; Regalo, Simone C.H.; Nelson-Filho, Paulo; Bussaneli, Diego G. [UNESP]; et al. (MDPI, 2020)
Bruxism is a masticatory muscle activity characterized by grinding of the teeth and clenching of the jaw that causes tooth wear and breakage, temporomandibular joint disorders, muscle pain, and headache. Bruxism occurs in both adults and children. Clinical characteristics and habits were evaluated in an adult sample. Moreover, we used DNA samples from 349 adults and 151 children to determine the presence of association with specific genes. Genomic DNA was obtained from saliva. The markers rs2241145 and rs243832 (metalloproteinase 2 (MMP2)), rs13925 and rs2236416 (metalloproteinase 9 (MMP9)), and rs6269 (cathecol-o-methyltransferase (COMT)) were genotyped. Data were submitted to statistical analysis with a significance level of 0.05. In adults, in univariate logistic regression, presence of caries, attrition, and use of alcohol were increased in bruxism individuals (p < 0.05). In addition, in adults, there was an association between bruxism and MMP9 (rs13925, p = 0.0001) and bruxism and COMT (rs6269, p = 0.003). In children, a borderline association was observed for MMP9 (rs2236416, p = 0.08). When we performed multivariate logistic regression analyses in adults, the same clinical characteristics remained associated with bruxism, and orthodontic treatment was also associated, besides rs13925, in the AG genotype (p = 0.015, ORa: 3.40 (1.27–9.07)). For the first time, we provide statistical evidence that these genes are associate with bruxism.
Keywords: Biomarkers; Child dentistry; Genetics; Matrix metalloproteinases; Oral diagnosis; Temporomandibular disorders